Comparison of accelerometer measured levels of physical activity and sedentary time between obese and non-obese children and adolescents: a systematic review - Rabha Elmesmari; Anne Martin; John J. Reilly; James Y. Paton (BMC, 2018)
Abstract Background Obesity has been hypothesized to be associated with reduced moderate-to-vigorous physical activity (MVPA) and increased sedentary time (ST). It is important to assess whether, and the extent to which, levels of MVPA and ST are suboptimal among children and adolescents with obesity. The primary objective of this study was to examine accelerometer-measured time spent in MVPA and ST of children and adolescents with obesity, compared with MVPA recommendations, and with non-obese peers. Methods An extensive search was carried out in Medline, Cochrane library, EMBASE, SPORTDiscus, and CINAHL, from 2000 to 2015. Study selection and appraisal: studies with accelerometer-measured MVPA and/or ST (at least 3 days and 6 h/day) in free-living obese children and adolescents (0 to 19 years) were included. Study quality was assessed formally. Meta-analyses were planned for all outcomes but were precluded due to the high levels of heterogeneity across studies. Therefore, narrative syntheses were employed for all the outcomes. Results Out of 1503 records, 26 studies were eligible (n = 14,739 participants; n = 3523 with obesity); 6/26 studies involved children aged 0 to 9 years and 18/26 involved adolescents aged 10.1 to19 years. In the participants with obesity, the time spent in MVPA was consistently below the recommended 60 min/day and ST was generally high regardless of the participant's age and gender. Comparison with controls suggested that the time spent in MVPA was significantly lower in children and adolescents with obesity, though differences were relatively small. Levels of MVPA in the obese and non-obese were consistently below recommendations. There were no marked differences in ST between obese and non-obese peers. Conclusions MVPA in children and adolescents with obesity tends to be well below international recommendations. Substantial effort is likely to be required to achieve the recommended levels of MVPA among obese individuals in obesity treatment interventions. This systematic review has been registered on PROSPERO (International Database of Prospective Register Systematic Reviews; registration number CRD42015026882).